2015
DOI: 10.1002/app.42748
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic characterization of conductive epoxy resin/polyaniline composites

Abstract: This study presents the ultrasonic characterization of conductive epoxy resin (ER)/polyaniline (PANI) composites. The prepared PANI is mixed with ER matrix at weight percentages of 5%, 10%, and 15% for preparing the ER/PANI composites. The effects of PANI amount on the mechanical properties of ER/PANI composites are investigated by ultrasonic pulse‐echo‐overlap method. Also, electrical conductivity, ultrasonic wave velocity and ultrasonic micro‐hardness values of ER/PANI composites are correlated. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Time of flight measurement process using the PEOM 55 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…Time of flight measurement process using the PEOM 55 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…Ramasamy et al synthesized PPy‐grafted graphene sheets (GS) via chemical oxidative polymerization with different weight ratios of GS:PPy (90:10, 50:50, and 25:75) and measured electrical conductivities of 26, 14, and 0.4 S/m, respectively. Xiao et al and Oral et al reported the polymerization of PANI via chemical oxidative polymerization. They determined that the conductivity of PANI was 406 and 59 S/m, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in electrical conductivity compared to the conductivity of unsubstituted PANI is due to overall decreases in contribution of both intrachains and interchains to the whole conductivity. Although poly(N-alkylanilines) are highly processable, their low electrical conductivities restrict their potential applications [59].…”
Section: Solution Blending Methodsmentioning
confidence: 99%